Tatalaksana Penyakit Glositis Atrofi akibat Defisiensi Zat Besi dan Vitamin B12 - Naoval Afif, Muhammad Yusril (Lombok Medical Journal, 2023)
Introduction : Atrophic glossitis is a disease of the tongue that causes inflammation or inflammation, then gives the appearance of a red tongue color with a smooth dorsum accompanied by pain and burning. Atrophic glossitis occurs when the fungiform and filiform papillae on the dorsum of the tongue are lost by as much as 50%. This is due to sufferers who have nutritional deficiencies, such as deficiency of B12, iron, folic acid, riboflavin, and niacin. This article aims to determine the general and specific management of atrophic glossitis. Method : The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were conducted on online journal publication portals such as MedScape, Google Scholar (scholar.google.com) and the National Center for Biotechnology Information (ncbi.nlm.nih.gov), with the keyword "Myasthenia Gravis". Discussion : Management of glossitis can be given with mouthwash containing corticosteroids and lidocaine to relieve inflammation. Then eat foods that contain vitamin B12. Conclusion : Atrophic glossitis can heal on its own and does not require treatment, but this should not be left alone, and requires good management/treatment, namely by maintaining good oral hygiene, then providing iron and vitamin B12 supplementation. Keywords: Glossitis Atrophy, Deficiency of vitamin B12